Equivalence and Loss in Literary Translation - Shahzoda Baxriddinova; Xayriyeva Madina (Journal of Innovation in Education and Social Research, 2025)
The act of translating literature is an intricate balancing act between maintaining equivalence with the original text and accepting inevitable losses that occur in meaning, style, and cultural nuance. This article explores the dual challenges of striving for fidelity while managing the realities of loss during the translation process. Through a qualitative analysis of translation theories and case studies of Italian and Uzbek literary works, this research investigates the complexities of transferring literary beauty across languages. The findings demonstrate that while complete equivalence is unattainable, strategies such as dynamic equivalence, cultural adaptation, and the translator’s creative mediation can minimize loss and preserve the spirit of the original text. This study contributes to a deeper understanding of the artistic and ethical responsibilities of literary translators and proposes best practices for enhancing cross-cultural literary communication.